Optimum Transmitter Receiver Ratio for Maximum Wireless Energy Transfer - Mohamad Harris Misran; Sharul Kamal Abdul Rahim (Institute of Advanced Engineering and Science, 2017)
Due to high demand of using cordless mobile device, the interest in wireless energy transfer (WET) has been growth intensively. This paper presented a method to obtained optimum transmitter receiver ratio for maximum performance of WET system using different initial antenna size at various distance. An optimized algorithm has been developed to determine the optimum ratios that yield the highest wireless transfer efficiency (WTE) at near field communication (NFC) frequency, 13.56MHz. 30mm x 30mm single square loop antenna is used as initial size of both transmitter and receiver using FR4 with operating distance = 50mm. Operating distance and initial size of the antenna will be varied and the effect to the WTE will be studied using Matlab, verified using Microsoft Studio CST. At distance = 50mm and initial size of the antenna = 30mm x 30mm, optimum transmitter to receiver ratio equal to 1:3 is obtained. The pattern of optimum transmitter receiver ratio between Matlab and CST has met an agreement. This research limited to integer transmitter receiver ratio used only and no decimal number being involved in magnify the transmitter size.